Opposite motion of the Central Helices of efflux pump KmrA is important for its export efficiency. (June 2022) - Li, Ying; Wen, Honglin; Ge, Xizhen
Abstract: Efflux pump of Major Facilitator Superfamily (MFS) is widely distributed in bacteria, while its role in regulating antibiotic resistance of nosocomial pathogen Klebsiella pneumoniae remains unclear. Herein we analyzed the effect of amino acid substitution of MFS efflux pump KmrA on its export efficiency via molecular biology and molecular dynamics (MD). After searching across the 804 sequenced K. pneumoniae isolates, we identified four major variants of KmrA, while one of them KmrA-A was demonstrated an inactive one in MIC and ethidium bromide efflux assays. Subsequently, MD simulations of KmrA and its variants were conducted and the opposite motion of the central helices were observed for the active variants, while it was not found for KmrA-A. To further identify the importance of the opposite motion to the conformational transition, we calculated their differences in volume of binding pocket, salt bridge and hydrophilic interaction with water based on the rocker-switch model. Our results indicated that the opposite motion of KmrA conferred a larger binding pocket and stronger hydrogen bond with water at inward-facing conformation. An unusual substitution S374A of KmrA-A disrupted the normal motion of central helices by enhancing hydrophobic interactions between them, resulting into the altered positions and strengths of salt bridge, which was deduced to affect the conformational transition. Overall our data provided detailed information on the regular of KmrA's moving trajectory, demonstrating the importance of opposite motion of central helices to KmrA's export efficiency. Highlights: The roles of MFS efflux pump KmrA in regulating antibiotic resistance of Klebsiella pneumoniae were confirmed. KmrA's variations across 804 K. pneumoniae were obtained and analyzed. Molecular dynamics investigation of KmrA and its variants identified the importance of opposite motion of central helices. The impact of the opposite motion on KmrA's conformational transition was investigated.